Umbilical Venous Catheter Update: A Narrative Review Including Ultrasound and Training - D'Andrea, Vito; Prontera, Giorgia; Rubortone, Serena Antonia; Pezza, Lucilla; Pinna, Giovanni; Barone, Giovanni; Pittiruti, Mauro; Vento, Giovanni (Frontiers in Pediatrics, 2022)
The umbilical venous catheter (UVC) is one of the most commonly used central lines in neonates. It can be easily inserted soon after birth providing a stable intravenous access in infants requiring advanced resuscitation in delivery room or needing medications, fluids, and parenteral nutrition during the first days of life. Resident training is crucial for UVC placement. The use of simulators allows trainees to gain practical experience and confidence in performing the procedure without risks for patients. UVCs are easy to insert, however when the procedure is performed without the use of ultrasound, there is a quite high risk, up to 40%, of noncentral position. Ultrasound-guided UVC tip location is a simple and lernable technique and therefore should be widespread among all physicians. The feasibility of a targeted training on the use of POCUS for UVC placement in NICU among neonatal medical staff has been demonstrated. On the other hand, UVC-related complications are very common and sometimes can be life-threatening. Despite UVCs being used by neonatologists for over 60 years, there are still no standard guidelines for assessment or monitoring of tip location, securement, management, or dwell time. This review article is an overview of the current knowledge and evidence available in the literature about UVCs. Our aim is to provide precise and updated recommendations on the use of this central line.